Advancing Transdisciplinary Research: The Transdisciplinary Research on Energetics and Cancer Initiative - Gehlert, Sarah (2014)
Strategies for constructing and maintaining cross-disciplinary teams are in their infancy. We outline strategies to support one form, transdisciplinary research, in a major initiative of the National Cancer Institute, the Transdisciplinary Research in Energetics and Cancer 2 (TREC2) initiative. Discussion of the TREC2 sites’ experiences with transdisciplinarity is structured around a conceptual model that identifies four iterative phases of transdisciplinary research. An active coordination center, regular face-to-face meetings, and input from external advisors were instrumental in moving TREC2 to the translation phase. The possibilities for advancements in the science of energetics and cancer increased as investigator ties became denser. TREC2 can be seen as a flagship effort in transdisciplinary science that provides lessons on moving ideas from development to translation.